Treasonous repertoires: Performing collaboration and musical life in Japanese-occupied Beijing, 1937–1945 - Schröder, Laura Odila (2022)
This thesis explores the musical culture of the “occupation state” in Japanese-occupied Beijing during the Second Sino-Japanese War (1937–1945). While cultural production in support of resistance against the Japanese in wartime China is well explored and its memory propagated to boost the CCP’s legitimacy, music composed and performed in support of the occupation state in Japanese-occupied China has largely been disregarded or dismissed. This thesis thus lies at the hitherto uncharted intersection of several areas of research, including wartime “collaboration”, the cultural history of Japanese-occupied north China, the development of music in wartime China, and musical culture of occupation more broadly. What can we learn about the occupation state in north China through an analysis of the musical repertoires and performance practices it developed and appropriated, and how does accounting for the musical culture of the occupation state alter our understanding of musical culture in wartime China? To address these questions, I draw on a broad range of sources, including musical scores, performance programmes and campaign reports published in the occupation state’s main news outlets, as well as archival material pertaining to the regime’s propaganda policies, music textbooks, a private collection of wartime concert programmes, musicians’ (auto)biographies and recordings. The first three chapters offer an overview of the occupation state, as well as its organization, ideologies and main campaigns in north China. They also provide a critical view of the historiography of music in twentieth century China, explaining the significance of this thesis as an intervention into dominant narratives, and a detailed account of the musical infrastructure in Japanese-occupied Beijing. The second part of the thesis offers a detailed musical analysis of the evolving musical repertoires and performance practices developed and appropriated by the regime with a particular focus on “new music”. I also consider how the regime employed collective and individual gendered voices and the spatial aspects of sound. I show how the song commission and mass singing activities initiated by the occupation state, as well as local musical elites’ concern for topical repertoire and voices, were surprisingly similar to musical developments in both pre-war China and in the non-occupied areas in wartime China. Such continuities and similarities draw into question long-standing narrative alignments between the aesthetic and moral judgement of musical culture in wartime China. I further show how musical repertoire and practice reflects changes and dissonances in the occupation state’s relationship with its citizens and reveals the regime’s attempts at mitigating the limitations of its territorial control, countering the normalization of the condition of occupation, and forging a distinctly local identity for itself through concert programme design. This analysis of the musical culture of the occupation state in north China thus contributes not only to our understanding of the cultural history of the occupation state in Japanese-occupied north China, but to broader discussions of musical culture in twentieth-century China and the role of music in shaping military occupations more broadly.